Optimization of Coagulation Pretreatment Conditions in a Ceramic Membrane System. Issue 12 (1st December 2015) - Alansari, Amir; Selbes, Meric; Karanfil, Tanju; Amburgey, James
Abstract : The goal of this project was to identify optimal coagulation pretreatment conditions and cleaning protocols in a pilot‐scale ceramic membrane system. A matrix of coagulation conditions (coagulant dose and pH) was investigated using aluminum sulfate and ferric chloride at two source waters (river and lake). Increasing backwash frequency to every 30 min and selecting a 30‐s interval proved to be critical since it reduced the effects of irreversible fouling during operation. After optimizing the clean‐in‐place procedure, the membranes were consistently recovered to 4 to 5 psi after the cleaning process. Results showed that optimal pretreatment conditions with aluminum sulfate reduced membrane total fouling rates by at least 80% relative to the control train. Optimal pretreatment with ferric chloride reduced membrane total fouling rates by 95% relative to the control train; however, the pretreatment conditions in which ferric chloride was effective were narrow compared with aluminum sulfate.